Risk Factors and Prevalence of Urinary Incontinence in Elderly Women, a Case Study in Japan and Taiwan - Hewiz, Alya Shafira; Widajanti, Novira; Hakim, Lukman; Satyawati, Rwahita (Journal Medical Informatics Technology, 2023)
Knowledge of the conditions of elderly women in Japanese and Taiwanese communities, particularly in relation to risk factors and their association with urinary incontinence, is of interest. This study aimed to identify risk factors and prevalence of urinary incontinence in elderly women in the community of the Japanese and Taiwanese case study areas. The research method used was a systematic review based on PRISMA guidelines. Data sources were obtained from PubMed and Science Direct for the period 2000-2020 using specific inclusion and exclusion criteria. Evaluation was conducted for quality and bias risk using a standardized assessment system. Results showed that the prevalence of urinary incontinence in elderly women in Japanese and Taiwanese communities ranged from 29.8% to 31.3%. Many factors influenced urinary incontinence, such as age, body mass index (BMI), and smoking habits. From the two selected articles in Japan and Taiwan, it was concluded that urinary incontinence was commonly experienced by elderly women in the community, and awareness of this condition could help improve management.